Centre d'Art Contemporain Fri-Art Kunsthalle 2000. - Bacchetta, Véronique; Bourriaud, Nicolas; Bovier, Lionel; Eppstein, Esther; Fabbri, Paolo; Fleck, Robert; Gonzalez-Foerster, Dominique; Höller, Carsten; Lux, Harm; Nicol, Michelle; Obrist, Hans-Ulrich; Parreno, Philippe; et al. (Fribourg : FRI-ART Centre d'Art Contemporain - Kunsthalle, 2000)
Bonvicini, Monica ; Closky, Claude ; Framis, Alicia ; Gillick, Liam ; Grigely, Joseph ; Heger, Swetlana ; Dejanov, Plamen ; Joseph, Pierre ; Kinmont, Ben ; Agence/Agentur ; Mercier, Mathieu ; Rawanchaikul, Navin ; Villesen, Gitte ; Büchel, Christoph ; Gramsma, Bob ; Lenzlinger, Jörg ; Steiner, Gerda ; Staub, Mirjam ; Tan, Fiona ; Tasset, Tony ; Wetzel, Markus ; Höller, Carsten ; Bonin, Cosima von ; Feldmann, Hans-Peter ; Gastaldon, Vidya ; Wicker, Jean-Michel ; Huber, Laurence ; Blanquet, Marie-José ; Stucki, Sidney ; Veilhan, Xavier ; Baudevin, Francis ; Belmont, Geraldine ; Dafflon, Stéphane ; Gygi, Fabrice ; King, Scott ; Klat ; Lambert, Alix ; Miller, John ; O'Neill, Amy ; Perret, Mai-Thu ; Bourban, Joseph ; Cianciolo, Susan ; RothStauffenberg ; Brener, Alexander ; Schurz, Barbara ; Capellari, Wolfgang ; Haring, Marlene ; Jermolaewa, Anna ; Minck, Bady ; Müller, Ariane ; Pomassl, Franz ; Trauttmansdorff, Octavian ; Bauer, Otmar ; Brus, Günter ; Nitsch, Hermann ; Roth, Dieter ; Rühm, Gerhard ; Wiener, Oswald ; à Wengen, Stefan ; Amadio, Anna ; Antille, Emmanuelle ; Bassanini, Katia ; Breuning, Olaf ; Carron, Valentin ; Engeler, Regula ; Favre, Geneviève ; Goei, Laurent ; Grego, Jasmin ; Hersberger, Lori ; Hess, Nic ; Huber, Laurence ; Lämmli, Dominique ; Lenzlinger, Jörg ; Lüber, Heinrich ; Moser, Frédéric ; Müller, Victorine ; Netzhammer, Yves ; Poloni, Marco ; Schreiber, Christoph ; Studer, Monica ; Stehlik, Bohdan ; Walther, Alexia ; Wildi, Ingrid
Duits & Engels & Frans
boek